KETERBUKAAN INFORMASI PUBLIK DAN KOMITMEN REFORMASI BIROKRASI - widiasthini, ni wayan (Jurnal Ilmiah Dinamika Sosial, 2017)
ABSTRACTPublic Information Openness is one of the commitments of bureaucratic reform, which is one of the point is to change the paradigm of bureaucratic closed toward open, and gave the waiter to the wider community. Public information openness is also a form of bureaucratic accountability to the program, achievements and performance targets to stakeholders, and obligations as a public institution. While the information is a service of rights owned by the community. There is a change in the pattern, both in terms of the applicant's information and public institutions as ruler of information, namely the use of information technology so that information requests can be served without limited space and time.Keywords: Public Information Openness and Bureaucratic Reform Commitment